AUTHENTICATION OF HALAL FOOD AND BEVERAGE PRODUCTS CERTIFIED BY BPOM AND LPPOM-MUI BASED ON NFC SMARTPHONE - Muhammad Rizal Fachri; Fathiah Fathiah (UIN Ar-Raniry, 2022)
In meeting the need for healthy food and drinks that have been verified as halal, the government has established BPOM (Food and Drug Supervisory Agency) and LPPOM MUI (Institute for the Assessment of Food, Drugs, Cosmetics, Indonesian Ulama Council) so that food products circulating are continuously monitored and halal maintained. Food and beverage products must be verified and rigorously tested by the two institutions, so that these food and beverage products can be labeled as halal and healthy. However, some foods and drinks that have not been verified as halal and healthy are still circulating among the public. To make it easier for the public and sellers of food and beverage products, they need a system that can see directly the food products that they are going to buy have been verified as halal and healthy. This research designs a system which can be used as input for practical and easy solutions in verifying halal products using NFC (Near-field communication). NFC is one of the smartphone features that has been widely applied lately. The use of this features can directly attach a smartphone at a distance about 0-2 cm to the product to be purchased and has been integrated with an NFC tag and only takes approximately 1-2 seconds to find out the product information from a smartphone that connected to the internet through the BPOM and LPPOM MUI websites.